2012
DOI: 10.1021/pr3001755
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Quantitative Phosphoproteomics: New Insights into Angiotensin-(1–7) Signaling Networks in Human Endothelial Cells

Abstract: Angiotensin-(1-7) [Ang-(1-7)] is an endogenous ligand of the Mas receptor and induces vasodilation, positive regulation of insulin, and antiproliferative and antitumorigenic activities. However, little is known about the molecular mechanisms behind these biological properties. Aiming to identify proteins involved in the Ang-(1-7) signaling, we performed a mass spectrometry-based time-resolved quantitative phosphoproteome study of human aortic endothelial cells (HAEC) treated with Ang-(1-7). We identified 1288 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
58
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 52 publications
11
58
0
2
Order By: Relevance
“…Ligand treatment with Ang(1-7) or AVE0991 in MAS-transfected cells couples calcium-independent activation of nitric oxide synthase to the phosphatidylinositol 3-kinase/protein kinase B, AKT pathway (Sampaio Verrilli et al, 2012;Savergnini et al, 2013;Than et al, 2013), or activation of phospholipase A2 (Santos et al, 2003b). Ang(1-7) altered the phosphorylation of MAP kinases (Sampaio et al, 2007a;Zimpelmann and Burns, 2009;Liu et al, 2012;Verano-Braga et al, 2012). Thus, Ang(1-7) action through MAS is proposed to be production of arachidonic acid and activation of nitric oxide synthase, which may not involve cAMP, IP3, and calcium signaling.…”
Section: Signalingmentioning
confidence: 99%
“…Ligand treatment with Ang(1-7) or AVE0991 in MAS-transfected cells couples calcium-independent activation of nitric oxide synthase to the phosphatidylinositol 3-kinase/protein kinase B, AKT pathway (Sampaio Verrilli et al, 2012;Savergnini et al, 2013;Than et al, 2013), or activation of phospholipase A2 (Santos et al, 2003b). Ang(1-7) altered the phosphorylation of MAP kinases (Sampaio et al, 2007a;Zimpelmann and Burns, 2009;Liu et al, 2012;Verano-Braga et al, 2012). Thus, Ang(1-7) action through MAS is proposed to be production of arachidonic acid and activation of nitric oxide synthase, which may not involve cAMP, IP3, and calcium signaling.…”
Section: Signalingmentioning
confidence: 99%
“…The need of such second messenger is also illustrated by the fact that 2 publications during the past years intensively investigated phosphorylation of intracellular molecules 28 and quantities of intracellular proteins, 29 respectively, in response to Ang-(1-7). Although aimed to identify useful molecules for receptor pharmacology, the data published failed to add useful tools to this approach.…”
Section: Discussionmentioning
confidence: 99%
“…4). Our recent phosphoproteomic study identified several further possible signaling pathways of cells induced by Ang-(1-7) stimulation, such as the Mas-Related Genes forkhead box protein O1 (Verano-Braga et al, 2012). It is not yet clear how these early signaling events induced by Ang-(1-7) are linked to the NO and phospholipase A 2 pathway.…”
Section: A Masmentioning
confidence: 99%